24‐hour ambulatory blood pressure alterations in patients with Parkinson's disease. Issue 1 (28th November 2021) - Shen, Liwei; Yang, Xiaoli; Lu, Wenmei; Chen, Weijie; Ye, Xiaofei; Wu, Danhong
Abstract: Objects: Abnormal blood pressure (BP) regulation is a feature of autonomic dysfunction in Parkinson's disease (PD) patients. The present study was to analyze the BP alterations by 24‐h ambulatory BP monitoring in PD patients with different disease stages and subtypes. Methods: 32 consecutive patients PD patients and 43 control patients in our hospital from 2017 to 2020 were included. The circadian BP rhythm was divided into three types according to the 24‐h ambulatory BP monitoring. Dipping was defined as an average systolic BP (SBP) reduction during night‐time of 10%–19%. Reverse dipping was defined as an average increase in night‐time SBP values. The differences of the circadian BP rhythm and BP variability (BPV) were analyzed between PD group and the control group, the early PD group and the advanced PD group, as well as the tremor‐dominant group and the nontremor‐dominant group. Results: There was statistical difference in circadian BP rhythm between PD group and control group ( p  < .05). There were statistical differences in circadian BP rhythm between the early PD group and the advanced PD group ( p  < .05). The mean values of night‐time SBP and diastolic BP (DBP) in the advanced PD group were higher than those in the control group and the early PD group ( p  < .05). The DBP CV in the advanced PD group was higher than that in the control group and the early PD group ( p  < .05). There was no significant difference of circadian BP rhythm, mean BP, and BPV between the tremor‐dominant and the nontremor‐dominant PD group after matching the disease duration. Conclusions: Reverse dipping was more common in PD patients in this study, especially in the advanced PD patients. 24‐h ambulatory BP monitoring is an important method to evaluate the BP alterations in PD patients. Clinicians should be alert to reverse dipping in PD patients and intervene to prevent serious clinical events. Abstract : This study was to evaluate the characteristics of blood pressure (BP) alterations in Parkinson's disease (PD) patients by 24‐h ambulatory BP monitoring. Reverse dipping was more common in PD patients in this study, especially in advanced PD patients. Clinicians should be alert to reverse dipping in PD patients and intervene to prevent serious clinical events.